Dom Casmurro à luz da onomástica : tramas e tramoias do romance machadianao - Santos, Bárbara da Silva (2016)
This master’s dissertation has the objective of making a onomastic analysis on the anthroponyms and toponyms used in the Machado de Assis’s novel, Dom Casmurro (1899), considering the relevance of the proper noun for the building of romance’s characters, its semantics and its setting. Our interpretation begins with the Plato’s dialogue, Cratylus, of which we highlight the legislator – or artificer –, wise man that, empowered by knowledge, would be able to give names based on the characteristics of what he names. In this sense, we are regarding the novel’s author as an artificer that names his personages and chooses, also influenced by the name, the spaces where the narrative action will be developed. We scan the novel’s nouns looking for a interpretation of the novel’s onomastics, through the etymology and the connotation that each name enables, trying, thereby, an approaching to meanings the Machado had wanted attribute to them. Therefore, we find support on the literary critics that gave attention for this romance’s aspect, having as biggest contribution Hellen Caldwell’s The Brazilian Othelo of Machado de Assis and one of its chapters completely dedicated to an onomastic analysis of Dom Casmurro. This writer, through this same piece, had opened a path for the Machado de Assis’s critics that we are joining to this work, formed by writers like John Gledson, Roberto Schwarz e Silviano Santiago, that identify in Bento Santiago’s memoirs narration the intention of making the reader his ally on the adultery indictment against Capitu, based on his writing style, as well as on his political and social formation. Keywords: Dom Casmurro; Machado de Assis; Onomasti.